(untitled) (Research, Society and Development, 2021)
Aminoglycosides are one of the therapeutic options used in the treatment of infections caused by multidrug-resistant gram-negative bacilli, including Acinetobacter baumannii strains. These bacterial species are considered an opportunistic pathogen that manage to develop resistance to aminoglycosides through enzymatic degradation by aminoglycoside modifying enzymes (AMEs) and 16S rRNA methylases. This study evaluated the occurrence of AMEs and methylases in a clinic isolates for aminoglycoside-resistant Acinetobacter spp from a hospital in Recife-PE, in addition to evaluating the clonal relationship among those compared. They were investigated as AMEs (aac (6’)-Ib, ant (2")-Ia and ant (3")- Ia) and as methylases (armA, rmtB, rmtC, rmtD, rmtF, rmtG) in 35 from Acinetobacter spp. resistant to one or more aminoglycosides, and ERIC-PCR was performed to determine the clonal relationship. Of the three AME genes studied, ant (3’)-Ia was the most prevalent gene present in 43% (15/35) of the following, followed by ant (2)-Ia with less than 1% (3 / 35), and the aac (6’)-Ib gene was not detected. Among the methylases, armA and rmtC were the most prevalent genes, with 80% (28/35) and 57% (20/35), respectively. The rmtB, rmtD, rmtF and rmtG genes were not detected. Molecular typing by ERIC-PCR described the occurrence of two clones in the hospital. The data obtained described an advance in resistance to aminoglycosides and the occurrence of genes detected with pattern similar to other previous studies, a clonality relationship among Acinetobacter spp. isolates that demonstrate diversity in the hospital environment and the neccessity for methods to prevention of dissemination of these clones in hospitals of Recife, Pernambuco.